Sequestration of phorbolesters by the aposematically coloured bug Pachycoris klugii (Heteroptera: Scutelleridae) feeding on Jatropha curcas (Euphorbiaceae) - Wink, Michael; Sporer, Frank (Chemoecology, 2000)
Summary. The phorbol ester DHPB has been detected in 5th instars and adults of Pachycoris klugii which feed on Jatropha curcas, a producer of phorbol esters with mollusc-, insect-, and vertebrate toxicity. DHPB from Pachycoris activates protein kinase C (PKC) which appears to be the main molecular target for phorbol esters. Phorbol esters of J. curcas exhibit a wide range of acute toxic effects in vertebrates and insects. It is therefore likely that the sequestration of DHPB, which would explain the aposematic colouration of the bugs, confers chemical protection to P. klugii against vertebrate predators.